Analysis of The Effectiveness of Corporate Criminal Liability Policies in Preventing Corruption in Indonesia - Cahyani, Gisella Tiara; Azzahra, Najwa Maulida; Hosnah, Asmak ul (Fakultas Hukum, Universitas Islam Bandung, 2024)
Corporate criminal liability policies have been implemented as a legal instrument aimed at preventing and combating corruption crimes in Indonesia. This policy is part of the government's efforts to strengthen corporate governance and enhance business integrity. However, the effectiveness of implementing this policy remains a subject of debate among legal experts and practitioners. Some critics argue that the policy has not significantly reduced corruption cases involving corporations. Factors such as lax law enforcement, gaps in regulations, and the inability of supervision systems are the main obstacles in the implementation of this policy. Additionally, a lack of awareness and commitment from corporate entities in applying principles of good corporate governance also influence the effectiveness of this policy. Therefore, there is a need for evaluation and improvement in the implementation of corporate criminal liability policies to be more effective in preventing corruption crimes in Indonesia.